Guideline for Technical Quality Assurance (TQA) of Ultrasound devices (B-Mode) – Version 1.0 (July 2012) - Kollmann, C.; deKorte, C.; Dudley, N. J.; Gritzmann, N.; Martin, K.; Evans, D. H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
The Technical Quality Assurance group was initiated by the EFSUMB Board in 2007 and met firstly in 2008 to discuss and evaluate methods and procedures published for performing technical quality assurance for diagnostic ultrasound devices. It is the aim of this group of experts to advise the EFSUMB Board of effective and efficacious methods for routine use and to make recommendations regarding the technical aspects of EFSUMB by-law 9, parts 11.6. & 11.7. The group´s work focused on new developments and related European projects to establish a common guideline. There is a great need of a well established protocol and dedicated processing software for the performance testing of medical ultrasound equipment. The measurements should be user independent as much as physically possible. Only if these goals are achieved in an international (firstly European) context, the optimal quality of ultrasound imaging can be offered and maintained to the medical community. This guideline aims to offer and summarize suitable procedures and evaluation processes to lend support for an optimal Technical Quality Assurance (TQA) scheme. The content of this guideline was presented to the EFSUMB Board of Directors (delegates) and approved by the EFSUMB Executive Board (ExB) at the regular meeting during EUROSON 2012 in Madrid April 2012.
Keywords: ultrasound; QA/QC; safety; technical aspects; physics